The association between meeting physical activity guidelines and academic performance among junior high school adolescents in China-evidence from the China education tracking survey - Yang, Jie; Wang, Hai; Luo, Lin (Frontiers in Psychology, 2023)
Purpose To examine how well Chinese adolescents meet the physical exercise time and screen time recommendations in the Physical Activity Guidelines for Chinese Residents (2021), and the relationship between adolescents’ physical exercise time, screen time and their academic performance. Method Daily physical exercise time, screen time and academic performance were collected from Grade 8 adolescents (n = 9,449). Academic performance included standardized scores on Chinese, Math and English tests and responses to the School Life Experience Scale. Results Meeting the physical activity time and screen time in the Physical Activity Guidelines for Chinese Residents was associated with adolescents’ academic performance. Specifically, having at least 60 min of physical exercise per day was associated with adolescents’ school life experiences compared to adolescents who did not meet the physical exercise time and screen time in the Chinese Residents’ Physical Activity Guidelines. Less than 2 h of cumulative screen time per day was associated with adolescent mathematics test scores, English test scores and school life experiences. Meeting both physical exercise time and screen time to be recommended had more significant effects on adolescents’ mathematics, Chinese, English and school life experiences. Meeting both the physical exercise time and screen time recommendations in the Physical Activity Guidelines for Chinese Residents was more significantly associated with boys’ mathematics test scores, Chinese test scores and School life experience. Meeting both the physical exercise time and screen time requirements in the Physical Activity Guidelines for Chinese Residents had a more significant effect on School life experience for girls. Conclusion Physical exercise participation of at least 60 min per day and/or less than 2 h of cumulative screen time per day were both associated with adolescent academic performance. Stakeholders should actively promote adolescents to follow the Physical Activity Guidelines for Chinese Residents (2021).